Pengaruh Pengetahuan Calon Pengantin Sebelum dan Setelah diberikan Pendidikan Gizi 1000 HPK Melalui Media Presentasi dan Booklet - Jihan Fadhilah Arsyad; Yuli Setiawaty; Yusnidar Yusnidar (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Early stunting prevention efforts must be made to break the chain of stunting spread. Objective: To find out whether there is an effect of knowledge of the prospective bride and groom before and after being given 1000 HPK nutrition education through presentation media and booklets. Method: Pre Experiment design where there is no control variable. This study used a non-randomized one-group pre-post test design, with 26 respondents with various educational backgrounds. Results: Statistical tests showed that there was a significant effect (p-value 0.000) of giving 1000 HPK nutrition education with presentation media and booklets to prospective brides before and after being given treatment. Conclusion: After being given health education, the average knowledge of the prospective bride and groom increased by more than 50% compared to the average before being given 1000 HPK nutrition education.